Murder in Highbury - Kelly, Vanessa (Kelly, Vanessa. Emma Knightley mystery, 2024)
Less than one year into her marriage to respected magistrate George Knightley, Emma has grown unusually content in her newfound partnership and refreshed sense of independence. The height of summer sees the former Miss Woodhouse gracefully balancing the meticulous management of her elegant family estate and a flurry of social engagements, with few worries apart from her beloved father's health . . .